The development of an emotion lexicon for the coffee drinking experience - Bhumiratana, Natnicha (Kansas State University, 2010)
Coffee is the most consumed beverage after water and the second widely traded commodity after crude oil. In the past decade or so the market for coffee has exploded. It is no longer competitive for the coffee industry to offer consumers just a ‘good’ cup of coffee. Coffee is mainly consumed for enjoyment and offers consumers the desirable emotional experience. Currently not much work has been done to capture the emotion experiences elicited by coffee drinking, which led to our objective: to identify and assess the feelings that are stimulated by the coffee drinking experience through the development of an emotion lexicon. In the first part of the study, focus groups were utilized to generate and fine-tune a list of emotions that occur during the coffee drinking experience. The list of terms was further refined by check-all-that-apply method, resulting in 86 emotions, which included 39 terms from a recently published emotion lexicon for food. In the second part of the study, this lexicon of 86 emotions was used to evaluate six coffee samples of various origins and degrees of roasting with 94 consumers. The emotion intensities before and during drinking were assessed. Consumers were clustered into six clusters based on the acceptability scores, and the appropriate emotions for distinguishing the coffee samples were determined by Stepwise Regression Analysis, which resulted in 44 emotions. Emotion maps for each consumer cluster constructed using Principal Components Analysis revealed that each sample generated distinctive emotional responses, which varied across each cluster. The last part focused on identifying the sensory drivers of emotions to understand the consumer’s perceptions because emotional and sensory experiences determine acceptability and consumption of coffee. Two separate highly-trained panels (a general panel and a coffee panel) performed descriptive analysis of the six coffee samples. After comparing the two panels, the coffee-specific panel data was used to identify the sensory attributes that might be responsible for eliciting certain emotions in the consumers. For instance, darker roasts seem to elicit positive-high energy emotions. Overall, this study is a stepping stone for more in-depth product-specific emotion studies in future.
Keywords: Emotion; Coffee; Agriculture, Food Science and Technology (0359)